Characteristics of Students in Physics Learning: Learning Motivation, Learning Styles, and Learning Experiences at Senior High School in Padang City - Ahzari, Serli; Nabila, Putri; Yulianda; Desnita; Usmeldi (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research aims to analyze the characteristics of students in physics learning, focusing on learning motivation, learning styles, and learning experiences. The research employs a descriptive method with a questionnaire as the instrument, distributed to 54 high school student respondents in Padang City. The data is analyzed quantitatively based on the percentage score for each indicator. The results show that students' learning motivation falls into the good category (73%), the most dominant learning style is kinesthetic (75%), and learning experiences indicate that the use of smartphones and whiteboards has the highest percentage (74%). It can be concluded that the characteristics of students demonstrate good learning motivation, diverse learning style preferences with kinesthetic and audio-visual tendencies, and learning experiences that have started to utilize information technology. It is suggested to develop more interactive learning strategies, integrate various learning media, and accommodate diverse learning styles to enhance the effectiveness of physics learning.